Pemberdayaan Santri Melalui Pojok Konseling Dalam Pencegahan Bullying Di Pondok Pesantren - Iin Aini Isnawati; Rizka Yunita (CV. Multi Kreasi Media, 2024)
Adolescence is a transition period from childhood to adulthood. Adolescence starts from the age of 11 – 20 years and is divided into 3 phases, namely: Early phase (11-14 years), Middle phase (15-17 years) and late adolescent phase (18-20 years). Some teenagers show their identity with aggressive behavior in order to be accepted by the group. The form of aggressiveness that is most often carried out by teenagers is verbal aggressiveness. Several studies show that teenagers who engage in verbal aggressiveness have low levels of satisfaction, poor family backgrounds, and low self-esteem. Case data from 2011 to 2019 for bullying was 2,473 cases, with an increasing trend. The aim of this service is to use counseling corner intervention and also reduce verbal aggressiveness, by forming a peer group model that has been previously established with and supporting facilities, this room is used for peer groups to identify problems and also provide solutions to perpetrators and victims of bullying. . The result of this activity was a decrease in the number of students who carried out and were victims of bullying in Islamic boarding schools from 125 students who felt bullied in the last 3 months to 10 children who had problems with friends and this had an impact on students' activeness in participating in activities and also in behaving with her friends. This counseling activity needs to be followed up as a means of support in monitoring and developing students in behaving and politely in Islamic boarding schools.